2020
DOI: 10.1016/j.celrep.2020.107925
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Maturation Media Improve Physiological Function of Human iPSC-Derived Cardiomyocytes

Abstract: SUMMARY Induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs) have enormous potential for the study of human cardiac disorders. However, their physiological immaturity severely limits their utility as a model system and their adoption for drug discovery. Here, we describe maturation media designed to provide oxidative substrates adapted to the metabolic needs of human iPSC (hiPSC)-CMs. Compared with conventionally cultured hiPSC-CMs, metabolically matured hiPSC-CMs contract with greater fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
252
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(303 citation statements)
references
References 61 publications
(69 reference statements)
7
252
0
1
Order By: Relevance
“…Altogether, these experimental results are consistent with the prediction of the simulations that pre-treatment with MM increases the SR Ca 2+ store, and its contribution to the cytosolic Ca 2+ transient that fuels contraction. These results are internally consistent with the results of our simulations, and with previous work where matured hiPSC-CM exhibited a more marked calcium decay time in response to thapsigargin 36 . In previous studies, maturation media containing dexamethasone and triiodothyronine 66 , and maturation induced by continuous field pacing 23 have been linked to improvements in hiPSC-CM Ca 2+ handling through formation of T-tubules.…”
Section: Mathematical Modeling Of the Ion Channel And Calcium Transiesupporting
confidence: 93%
See 2 more Smart Citations
“…Altogether, these experimental results are consistent with the prediction of the simulations that pre-treatment with MM increases the SR Ca 2+ store, and its contribution to the cytosolic Ca 2+ transient that fuels contraction. These results are internally consistent with the results of our simulations, and with previous work where matured hiPSC-CM exhibited a more marked calcium decay time in response to thapsigargin 36 . In previous studies, maturation media containing dexamethasone and triiodothyronine 66 , and maturation induced by continuous field pacing 23 have been linked to improvements in hiPSC-CM Ca 2+ handling through formation of T-tubules.…”
Section: Mathematical Modeling Of the Ion Channel And Calcium Transiesupporting
confidence: 93%
“…Strikingly, this media had opposing effects on the action potential duration of genetically unique hiPSCderived tissue chips, with the net result of forcing both genotypes towards an actional potential duration range that is typical for adult human ventricular cardiomyocytes. These results suggest that, as in monolayer culture of hiPSC-CM 36 , maturation with fatty-acid based media may be a prerequisite to using hiPSC-CM based tissue chips to predict how drugs will affect the adult human heart.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It was shown that high glucose concentrations can reduce mitochondrial function [ 16 ], while excluding glucose from the medium favors the metabolic switch to mitochondrial oxidative phosphorylation [ 13 , 17 ]. Also, Feyen and collaborators demonstrated that the inclusion of oxidative substrates to the culture medium of iPSCs-CM produce metabolically mature CMs, improving electrophysiological and mechanical parameters [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Unlike adult cardiomyocytes, neonatal or iPSC cardiomyocytes do not show rectangular morphology, exhibit spontaneous generation of AP, have lower density of mitochondria and higher dependence on glycolytic metabolism over fatty acid oxidation. Several recently developed techniques help iPSC-CM maturation through metabolic supplementation ( Parikh et al, 2017 ; Feyen et al, 2020 ), incremental pacing ( Chan et al, 2013 ) and culture substrate modifications to promote higher contraction forces ( Pandey et al, 2018 ). Currently, these culture procedures from somatic reprogramming to obtaining functionally mature iPSC-CMs require over a month’s time, which may limit their use for point-of-care testing.…”
Section: Addressing Functional and Cellular Heterogeneity In Cardiomymentioning
confidence: 99%